Personal finance: the influence of finance disciplines on the financial behavior of business administration students at a public university - Silva, Valdilene Gonçalves Machado (2023)
Financial Education provides citizens with the necessary knowledge about personal finances to make more assertive financial decisions. Thus, the present study aimed to analyze whether the finance disciplines studied during the Administration course at a Public University located in the Midwest of Minas Gerais influenced the financial behavior of students. For this purpose, descriptive research was carried out, with a qualitative and quantitative approach, using the case study. It was observed that the students who participated in the research were mostly female, single, had already entered the job market, were between nineteen and twenty-four years old and had a monthly income between R$1,101.00 and R$2,950.00. The results indicated that the Personal Finance content was not part of the syllabus of the Finance disciplines offered by the course. However, the theme was treated through the complementary activities developed in the disciplines. Thus, it can be seen that the hypothesis raised that finance disciplines contributed to students having a more conscious financial behavior was validated.